2008
DOI: 10.1021/ja8077076
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Generation and Reversible Cycloaromatization of a Nine-Membered Ring Cyclic Enediyne

Abstract: Irradiation of the nine-membered ring enediyne precursor, which has one of its triple bonds masked as cyclopropenone, efficiently (Phi = 0.34) generates the reactive 4,5-benzocyclonona-2,6-diynol. The latter rapidly equilibrates with the corresponding 1,4-didehydronaphthalene diradical and then undergoes rate-limiting hydrogen abstraction to produce the ultimate product of the Bergman cyclization, benz[f]indanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 107 publications
0
32
0
Order By: Relevance
“…[8][9][10] Their extraordinary reactivity and cytotoxicity have sparked considerable research and a great deal of efforts are being spent up to date to study the various factors influencing the Bergman cyclization. [11][12][13][14][15][16][17][18][19][20] In comparison with the pristine enediyne antitumor antibiotics cited above, neocarzinostatin (NCS) [21] although belonging likewise to the group of natural enediyne antitumor antibiotics contains a slightly different active chromophore, a dienediyne. [22] Like the natural enediynes, NCS shows a remarkable antitumor activity that is based on a related diradical cyclization.…”
Section: Thermal Diradical Cyclizations (Bergman Myers-saito)mentioning
confidence: 99%
“…[8][9][10] Their extraordinary reactivity and cytotoxicity have sparked considerable research and a great deal of efforts are being spent up to date to study the various factors influencing the Bergman cyclization. [11][12][13][14][15][16][17][18][19][20] In comparison with the pristine enediyne antitumor antibiotics cited above, neocarzinostatin (NCS) [21] although belonging likewise to the group of natural enediyne antitumor antibiotics contains a slightly different active chromophore, a dienediyne. [22] Like the natural enediynes, NCS shows a remarkable antitumor activity that is based on a related diradical cyclization.…”
Section: Thermal Diradical Cyclizations (Bergman Myers-saito)mentioning
confidence: 99%
“…For the preparation of the title compound, see: Ghorbani-Vaghei et al (2009). For its applications, see: Chen et al (2002Chen et al ( , 2006Chen et al ( , 2007; Chow et al (2005); Jansen et al (2010); Pandithavidana et al (2009); Swartz et al (2005). For related structures, see: Kuś & Jones (2003); Qin et al (2005); Sim et al (2001).…”
Section: Related Literaturementioning
confidence: 99%
“…The title compound and its derivatives are useful reagents to build a naphthalene ring (Chen et al, 2002(Chen et al, , 2006(Chen et al, , 2007Chow et al, 2005;Jansen et al, 2010;Pandithavidana et al, 2009). In addition, they have been prepared as potential precursors to pentacene derivatives (Swartz et al, 2005).…”
Section: S1 Commentmentioning
confidence: 99%
“…Later, Turro and Nicolaou revealed that simple artificial enediynes could also undergo cycloaromatization upon photo‐irradiation 45. Subsequently, plenty of arene‐fused or nonbenzenoid, locked or acyclic enediynes were explored and investigated under photoirradiation 46–56. Photo‐Bergman cyclization was deemed to be similar in mechanism to that of the thermal induced.…”
Section: Introductionmentioning
confidence: 99%